Optimalisasi Desain Atrium dan Façade Melalui Analisis Evakuasi Kebakaran dan Konsumsi Energi - Ola, Frengky B.; Wismarani, Yustina Banon; Karang, Anak Agung Ayu Ratih Tribhuana Adityadewi; Ilhamdi, Hana Zaskia (Universitas Medan Area, 2025)
Consideration of the use of the atrium and efforts to reduce room cooling energy were taken into consideration in the design process for the building for the faculty of technology and the department of civil engineering – UAJY. The performance study was carried out using a literature study and simulation approach to be taken into consideration in making design decisions. The atrium design study was carried out on two options, namely designs without and using an atrium. The study was conducted to see the role of the use of the atrium in optimizing natural lighting and fire smoke removal. Façade studies were carried out on four design options to see the performance of each option. Maximum use of the atrium has a positive impact on room lighting and room heat dissipation. The use of a sloping roof on the side where the wind comes from has a positive impact on the efforts to dissipate heat and smoke in the room. The use of a rectangular atrium also functions better in exhausting smoke compared to a box-shaped atrium. Four shading design models have been tested on building façade designs. These four models have a positive impact on reducing space cooling loads. However, a model with minimum performance was chosen, namely a combination of conventional shading with external horizontal blinds, but it is more efficient in terms of the use of materials, costs and building structure, and looks lighter visually.